Implementasi Manajemen Peningkatan Mutu di Perguruan Tinggl Islam - Bani Bani (Jurnal Kependidikan Islam, 2012)
Islamic education at oftentimes Indonesian front with various problem that don't demulcent. One of about problem education that don't demulcent and faced by incionesian ruition is ics low quality on each ladder and satuan is education, notably elementary education and intermediate. About position and upgrade rruinagement importance at an Islamic college is that hereafter existence a college (Islamic college) doesn't particularly clings to government, but preferably clings to estimation stakeholders (college student, oldster, job the world, government, lecturer, supporter energy, and dies interested parties other parties) about Islamyang's college quality be evened out. That its existence is secured, therefore unlikely college shall upgrade at Islamic college that be evened out Kata